Evaluasi Penggunaan Obat Antihipertensi pada Pasien Hipertensi Geriatri di Klinik Pratama Annisa Semarang - Angelina Crystin Puspitasari; Ovikariani Ovikariani; Gilang Rizki Al Farizi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Hypertension is a disease characterized by an increase in systolic blood pressure of more than 140mmHg and diastolic blood pressure of more than 90 mmHg. Hypertension is called the “silent killer” because it does not directly kill the sufferer but triggers other diseases such as heart attacks, strokes, and kidney failure. This study aims to determine the rationale for using antihypertensive drugs in geriatric hypertensive patients, including the right indication, the right dose, the right drug, and the right patient at the Annisa Pratama Clinic Semarang. The type of research used is descriptive non-experimental, with retrospective data collection in the form of patient medical record data; as many as 45 patients were taken as samples were analyzed based on the standard of therapy used, namely The Eight Joint National Committee (JNC VIII). The results showed that the characteristics of most respondents were at the age of 45-54, namely 25 people (55,6%), and the most respondents with stage 2 hypertension were 40 people (88,9%). The rationale for using antihypertensive drugs at the Annisa Pratama Clinic Semarang is 100% correct indication, 91,1% correct dose, 91,1% correct drugs, and 100% correct patient. The use of antihypertensive drugs in geriatric patients is appropriate according to the standard of therapy used based on JNC VIII.